Frontiers in applied mechanics - Liu, Zishun (Imperial College Press, 2015)
Frontiers in Applied Mechanics is a compilation of cutting-edge research in applied mechanics by 65 of the world's leading researchers and academics. It comprises current new research directions and topics in the field, as well as developments in the classical branches of applied mechanics; namely solid mechanics, fluid mechanics, thermodynamics, and materials science